Short term outcomes of the first round of a pilot colorectal cancer screening programme with guaiac based faecal occult blood test. Issue 11 (6th July 2007) - Denis, Bernard; Ruetsch, Marcel; Strentz, Patrick; Vogel, Jean Yves; Guth, Francis; Boyaval, Jean Marc; Pagnon, Xavier; Ebelin, Jean François; Gendre, Isabelle; Perrin, Philippe
Abstract : Objective: To assess both feasibility and short term outcomes of a population based colorectal cancer screening programme using a biennial guaiac based faecal occult blood test (gFOBT). Method: All participants were invited by mail to take part in a screening programme using a non-rehydrated gFOBT. The gFOBTs were first provided by general practitioners (GPs) and then directly mailed to individuals who failed to comply after two invitations. The setting was a French administrative district: Haut-Rhin (710 000 inhabitants). 182 981 residents aged 50–74 years were invited to participate. Results: 19 274 people (10.5%) were excluded from gFOBT screening and 90 706 completed a gFOBT, so that the participation rate was 55.4% of those eligible. 76.5% of the completed gFOBTs were provided by GPs and 15.5% by direct mailing. The gFOBT positivity rate was 3.4%. The positive predictive value was 42.7% for neoplasia (women 30.8%, men 52.5%), 23.6% for advanced adenoma, and 7.6% for cancer. The number of normal colonoscopic procedures (without neoplasia) needed to be performed for each colonoscopy detecting an advanced neoplasia was 1.8, lower in men (1.2) than in women (3.4), and decreasing with age. Detection rates for neoplasia and cancer were 12.8 and 2.3 per 1000 people screened. 206 adenocarcinomas were detected: 47.6% were stage I and 23.8% stage II. The direct cost was estimated at €29.3 per screened person and €13 466 per cancer detected. Conclusions: Participation and diagnostic yield of controlled trials of gFOBT screening are reproducible in the real world at an acceptable cost through an organised population based programme involving GPs.